Kotak Saran Online dan Gratis Untuk Penjaminan Mutu Berkelanjutan - Muhammad; Budi Kurniawan (Jurnal Informatika dan Komputer (JIK), 2022)
Feedback and suggestions are important for every institution to improve its quality, especially for higher education institutions which always strive to improve the quality of education in a planned and sustainable manner. One form of guarantee for higher education is the Internal Quality Assurance System (SPMI), apart from the External Quality Assurance System (SPME), and the Higher Education Database (PD Dikti). The form of implementation of SPMI is to carry out the SPMI cycle which consists of Determination, Implementation, Evaluation, Control and Improvement of Standards or what is known as PPEPP. Input or suggestions are part of the Evaluation other than Monitoring and Evaluation (Monev) which is carried out within a certain period which can be used as a self-evaluation for universities and study programs in improving sustainable quality. Input and suggestions are obtained from students by submitting them directly to related parties, or can be submitted through a suggestion box installed at the university or at the faculty. The suggestions obtained through the suggestion box physically have limitations, and changes in student behavior towards technological developments make students use smartphones and laptops more than using manual writing. Based on this, an online suggestion box was created which can be accessed widely anytime and anywhere. This research was created to produce a suggestion box online through a free application using the prototyping method